2022
DOI: 10.1016/j.ssmqr.2021.100035
|View full text |Cite
|
Sign up to set email alerts
|

Anticipating hopes, fears and expectations towards COVID-19 vaccines: A qualitative interview study in seven European countries

Abstract: Vaccine uptake is essential to managing the ongoing COVID-19 pandemic, and vaccine hesitancy is a persistent concern. At the same time, both decision-makers and the general population have high hopes for COVID-19 vaccination. Drawing from qualitative interview data collected in October 2020 as part of the pan-European SolPan study, this study explores early and anticipatory expectations, hopes and fears regarding COVID-19 vaccination across seven European countries. We find that stances towards COVID-19 vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 47 publications
4
22
0
Order By: Relevance
“…Still, sample non-representativeness implies our findings may not be generalizable to the UKEM healthcare worker population, White British/Irish healthcare workers, and the general lay population. It is noteworthy, however, that similar perspectives and evidence have been reported in previous healthcare worker and general population/community studies in the UK ( Kamal et al, 2021 ; Woodhead et al, 2021 ) and other countries ( Aw et al, 2021 ; Paul et al, 2022 ). Nonetheless, future studies are encouraged to use representative samples to enhance the external validity of findings.…”
Section: Resultssupporting
confidence: 81%
“…Still, sample non-representativeness implies our findings may not be generalizable to the UKEM healthcare worker population, White British/Irish healthcare workers, and the general lay population. It is noteworthy, however, that similar perspectives and evidence have been reported in previous healthcare worker and general population/community studies in the UK ( Kamal et al, 2021 ; Woodhead et al, 2021 ) and other countries ( Aw et al, 2021 ; Paul et al, 2022 ). Nonetheless, future studies are encouraged to use representative samples to enhance the external validity of findings.…”
Section: Resultssupporting
confidence: 81%
“…Low trust in government advice and recommendations due to its perceived handling of the pandemic and changing COVID-19 messaging was identified as a potential barrier to vaccine acceptability and uptake in our study and others 23 29–31. The link between mistrust in a COVID-19 vaccine and mistrust in government was found to be more pronounced among some ethnic minority groups in a small qualitative study among UK healthcare providers32 and a larger UK quantitative study 23.…”
Section: Discussionmentioning
confidence: 48%
“…A small qualitative UK parental study and larger survey completed in May 2020 found that COVID-19 vaccine safety and efficacy concerns were the greatest barrier to definite vaccine acceptance, which in the larger parallel survey was 56% 31. There was a belief that COVID-19 vaccine development had been rushed among most participants in our study and other qualitative studies 30 32. Some of our participants stated that they would wait until ‘it is deemed safe and effective’, or others in the population received the vaccine first before accepting it themselves.…”
Section: Discussionmentioning
confidence: 58%
“…Our results might therefore, be more transferable to countries with similar contexts, such as Austria and Switzerland. These German-speaking countries have substantial cultural, historical, and economic ties and share a similar system of federalism with mandatory universal health insurance [ 3 , 65 , 66 ]. While all three countries had prompt and similar governmental responses to the COVID-19 outbreak (school closures, obligatory masks, enforce social distancing, free testing facilities, contact tracing, etc.)…”
Section: Discussionmentioning
confidence: 99%